Pengaruh Media Sosial terhadap Karakter Pemuda Masa Kini - Netty Tesa Yolanika Sitompul (International Forum of Researchers and Lecturers, 2024)
Social media is not only a means of communication, but also influences the thinking patterns, behavior and social interactions of the younger generation. Thus, a deep understanding of the influence of social media on the character of today's youth is very important in the context of social and cultural development. This journal investigates the impact of social media use on youth character in the contemporary era. This research uses quantitative and qualitative methods to analyze the behavior, values, and self-perceptions of young people who are influenced by their interactions on social media platforms. The results show that intense exposure to social media can influence character formation, both positively and negatively. The psychological and social implications of social media use in today's youth are the main focus in this journal, providing in-depth insight into the role of social media in shaping the identity and character of the younger generation.